A linear model of fine enforcement with application to England and Wales - Lewis, Donald E. (Journal of quantitative criminology, 1988)
Fines are the most common sanction against criminal offenders in many countries. Economists have developed models for determining the optimal use of fines. Their models, however, generally abstract from problems of fine enforcement and assume that all fines are collected and that enforcement costs are zero. Criminologists and practitioners, on the other hand, have been very much aware of enforcement costs. Imprisonment for fine default is particularly costly and exacerbates the crowded prison conditions that exist in many countries. This paper extends previous economic models by dropping the limiting assumption of zero enforcement costs. The model is estimated using data from England and Wales and is used to evaluate alternative methods and levels of fine enforcement.